Apakah Pelatihan Berdampak pada Upah? Studi Kasus Survei Angkatan Kerja Nasional Tahun 2018 - Ardhian Kurniawati; Hennigusnia Hennigusnia (Jurnal Ketenagakerjaan, 2020)
Human capital is one of the important things in the competitiveness and economic growth of a country. It can be obtained through various ways, one of them through education and training. There are a lot of research focused on investment in returning human capital through education. This study tries to determine the impact of training on one's wages using data from the 2018 National Labour Force Survey. The Estimation using Mincerian Model with Ordinary Least Square (OLS). Estimation result show that training would increase wages by 12.15%. In addition this study also found differences in wage increases between men and women who have received training. Men who have received training tended to experience a 33.13% increase in wages compared to women who have received training.